Improving the Performance of Lead‐Free FASnI3‐Based Perovskite Solar Cell with Nb2O5 as an Electron Transport Layer. Issue 2 (2nd January 2023) - Hosen, Adnan; Mian, Md. Suruz; Ahmed, Sheikh Rashel Al
Abstract: In this work, the photovoltaic outputs of the lead‐free FASnI3 ‐based perovskite solar cells are discussed by using Solar Cell Capacitance Simulator in One Dimension. The device outputs estimated theoretically in this study are almost equal to the experimental results, thereby verifying accuracy of this simulation. To find the decent electron transport layer (ETL), herein, various ETLs are presented instead of C60 /BCP in the experimental FASnI3 ‐based perovskite solar cell (PSC). The designed FASnI3 PSC utilizing niobium pentoxide (Nb2 O5 ) as an ETL with an appropriate band alignment and a low lattice mismatch at FASnI3 /ETL interface provides better efficiency by decreasing recombination at front side. The performances of the proposed PSC are also measured by altering the thickness and doping of ETL and absorber, interface defects, and series and shunt resistances. Furthermore, this paper reports the calculation of recombination coefficients at absorber/ETL interface, depletion region, and quasi‐neutral region. An improved efficiency of 22.24% is evaluated at optimized thicknesses of 100 nm for HTL, 500 nm for absorber, 50 nm for ETL, and 50 nm for ITO for the proposed inverted PSC of ITO/PEDOT:PSS/FASnI3 /Nb2 O5 /Ag. These results suggest that chemically stable and less‐toxic Nb2 O5 can be applied as a useful ETL in inverted PSCs for further improving the performances. Abstract : Herein, a lead‐free FASnI3 perovskite solar cell (PSC) with Nb2 O5 electron transport layer is designed, and photovoltaic performances are evaluated through numerical tool. The proposed PSC provides better conversion efficiency by decreasing recombination at front side. An efficiency of 22.24% with V oc of 0.99 V, J sc of 28.55 mA cm −2, and fill factor of 78.86% is evaluated.